The Effect of Circuit Training Methods on Improving Aerobic Endurance in 10-12-Year-Old Volleyball Players - Rd. Muhammad Mulky Al Hakim; Dede Rohmat Nurjaya; Oktoviana Nur Ajid (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Volleyball is a game that is played continuously with short durations and high intensity, interspersed with brief recovery periods that occur sequentially during the match. The characteristics of the volleyball game require high endurance, making aerobic endurance training essential for the sustainability of athletes in developing their abilities, skills, and bodily endurance in order to adapt to the game which is played continuously with high intensity. This study aims to determine the effect of circuit training methods on the improvement of aerobic endurance. The method used is an experiment with a one-group pre-test and post-test design, with a sample size of 20 students aged 10-12 years who are active in the volleyball extracurricular at Limbangan Tengah 2 Elementary School. The research results show that there is a significant effect of circuit training methods on improving aerobic endurance in volleyball players aged 10-12 years. This is indicated by the average pretest score of 25.9850 and a posttest score of 42.8000, with a significance value of 0.000 < 0.005. Thus it can be concluded that there is a significant difference between the results of training with the circuit training method on the pretest and posttest data. Therefore, the circuit training method is very effective in improving aerobic endurance, which combines strength and endurance training by completing one group or circuit of exercises with minimal or no rest.